Perspective: National Football League Teams Need Chief Diversity Officers - DeMartini, Anne L.; Butler, Barbara Nalani (Frontiers in Sports and Active Living, 2022)
The National Football League (NFL) and its teams, some of the world's most profitable sporting properties, face challenges with diversity, equity, and inclusion (DEI). With a history of discriminatory work environments, including a recent high-profile lawsuit, the NFL and its teams have a poor reputation on these issues. This perspective piece investigated NFL teams' utilization of organization employees dedicated to DEI. Utilizing a content analysis of publicly available data, this piece investigated DEI employees at NFL team organizations. The study analyzed the position's characteristics including the name of the role, the department in which it was housed, and the reporting structure. The study also examined the demographics and professional background of the employees in the roles. The findings conclude that NFL teams lag behind other American businesses in their adoption of Chief Diversity Officer (CDO) roles. As of 2022, only 31.25% of NFL teams had a dedicated DEI staff person. Three additional teams host diversity councils utilizing employees with other job responsibilities. The employees filling the CDO roles were majority women and majority Black. Though not the only answer to a complex problem, in order to address these challenges and move forward, the NFL teams should create Chief Diversity Officer (CDO) roles. These positions should have appropriate reporting relationships, well-crafted position responsibilities, generous resources, and qualified and experienced employees.